The Diagnostic Test in Lumbosacral Vertebrae Image towards Magnetic Resonance Imaging in Radicular Low Back Pain - Dhimas Hantoko1, Isti Suharjanti1, Sri Andreani Utomo2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Lower back pain is one of the most common consulted cases in neurology and neurosurgery. The approximately 80% of these cases are musculoskeletal disorders. Magnetic resonance imaging (MRI) is still a rare examination in the suburban area and requires a relatively high cost. Moreover, there are contraindications in patients who have cardiac pacemakers and metal objects in the body. The examination of lumbosacral image is easy to conduct. The price is relatively inexpensive and there are no contraindications to perform the test. Objectivity: This study aimed to assess the sensitivity and specificity of the lumbosacral image towards MRI in patients with radicular lower back pain. Method: The study was a clinical, crosssectional study, analytical, and a diagnostic test design. It was performed on all patients with radicular lower back pain in Dr. Soetomo Teaching Hospital Surabaya from April to July 2012. There were 34 subjects who fulfilled the inclusion criteria. Results: The sensitivity of plain images to MRI in detecting radicular lower back pain was 87.5%. This figure indicated that the plain image had a high sensitivity. However, the specificity was only 50.0% which meant that plain image had a low specificity. Conclusion: The lumbosacral image had high sensitivity. However, the specificity was low for the examination of radicular lower back pain.